Penerapan Algoritma Bubble Sort Dalam Aplikasi Mobile Penentuan Nilai Prestasi Siswa - Resiana, Cindy Dinda; Wijaya, Yunan Fauzi; Darusalam, Ucuk (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
In high school, the aim is to improve the effectiveness and time efficiency of the student performance assessment process. The solution obtained is to use the bubble sort algorithm, which will be optimized to increase the performance of the bubble sort algorithm and generate more efficient results. In the implementation of the bubble sort algorithm for this research, the sorting is done in descending order, starting from the smallest value. Consequently, the first position with the highest value is obtained as "94" for Nurlita Hasibuan, and the lowest value is "56" for Hendro Mahardika. In this study, the optimization of the algorithm resulted in a time complexity of ???? (???? ????og (????)), which performed efficiently. The system testing in this research utilized the SUS method, and the final result obtained a SUS score of "83.95", which corresponds to a grade A with an Excellent rating.